Освіта національних меншин України (1990–2000-ні рр.) - Зеркаль, М.М. (Український історичний журнал, 2013)
Робиться спроба дослідити місце й роль освіти етноменшин у загальній ідеології державотворчих та суспільно-політичних трансформацій. Визначено
роль національно-культурних товариств, неурядових організацій, засобів масової інформації в розвитку полікультурних традицій навчання та виховання. Розглянуто нові форми діяльності початкових, середніх і спеціальних закладів
освіти з етнічним компонентом. In the article on the basis of facts, analytical materials, scientific arguments, authorial
conclusions an attempt to investigate a place and role of formation of ethnic minorities
in general ideology of state-creative and publicly is done – political transformation
of independent Ukraine. Certain role in development of multicultural traditions of
studies and education nationally – cultural societies, ungovernmental organizations,
mass medias. The considered new forms of activity of initial, middle and special
establishments of education are with an ethnic component.